DNAJB1-PRKACA fusion kinase interacts with β-catenin and the liver regenerative response to drive fibrolamellar hepatocellular carcinoma - Kastenhuber, Edward R.; Tschaharganeh, Darjus-Felix (Proceedings of the National Academy of Sciences of the United States of America, 2017)
A segmental deletion resulting in DNAJB1-PRKACA gene fusion is now recognized as the signature genetic event of fibrolamellar hepatocellular carcinoma (FL-HCC), a rare but lethal liver cancer that primarily affects adolescents and young adults. Here we implement CRISPR-Cas9 genome editing and transposon-mediated somatic gene transfer to demonstrate that expression of either the endogenous fusion protein or a chimeric cDNA leads to the formation of indolent liver tumors in mice that closely resemble human FL-HCC. Notably, overexpression of the wild-type PRKACA was unable to fully recapitulate the oncogenic activity of DNAJB1-PRKACA, implying that FL-HCC does not simply result from enhanced PRKACA expression. Tumorigenesis was significantly enhanced by genetic activation of β-catenin, an observation supported by evidence of recurrent Wnt pathway mutations in human FL-HCC, as well as treatment with the hepatotoxin 3,5-diethoxycarbonyl-1,4-dihydrocollidine, which causes tissue injury, inflammation, and fibrosis. Our study validates the DNAJB1-PRKACA fusion kinase as an oncogenic driver and candidate drug target for FL-HCC, and establishes a practical model for preclinical studies to identify strategies to treat this disease.